Amelioration of Acute Sequelae of Blast Induced Mild Traumatic Brain Injury by N-Acetyl Cysteine: A Double-Blind, Placebo Controlled Study - Hoffer, Michael E.; Balaban, Carey; Slade, Martin D.; Tsao, Jack W.; Hoffer, Barry (PloS one, 2013)
Mild traumatic brain injury (mTBI) secondary to blast exposure is the most common battlefield injury in Southwest Asia. There has been little prospective work in the combat setting to test the efficacy of new countermeasures. The goal of this study was to compare the efficacy of N-acetyl cysteine (NAC) versus placebo on the symptoms associated with blast exposure mTBI in a combat setting. This study was a randomized double blind, placebo-controlled study that was conducted on active duty service members at a forward deployed field hospital in Iraq. All symptomatic U.S. service members who were exposed to significant ordnance blast and who met the criteria for mTBI were offered participation in the study and 81 individuals agreed to participate. Individuals underwent a baseline evaluation and then were randomly assigned to receive either N-acetyl cysteine (NAC) or placebo for seven days. Each subject was re-evaluated at 3 and 7 days. Outcome measures were the presence of the following sequelae of mTBI: dizziness, hearing loss, headache, memory loss, sleep disturbances, and neurocognitive dysfunction. The resolution of these symptoms seven days after the blast exposure was the main outcome measure in this study. Logistic regression on the outcome of 'no day 7 symptoms' indicated that NAC treatment was significantly better than placebo (OR = 3.6, p = 0.006). Secondary analysis revealed subjects receiving NAC within 24 hours of blast had an 86% chance of symptom resolution with no reported side effects versus 42% for those seen early who received placebo. This study, conducted in an active theatre of war, demonstrates that NAC, a safe pharmaceutical countermeasure, has beneficial effects on the severity and resolution of sequelae of blast induced mTBI. This is the first demonstration of an effective short term countermeasure for mTBI. Further work on long term outcomes and the potential use of NAC in civilian mTBI is warranted. ClinicalTrials.gov NCT00822263.